X-Linked Myotubular Myopathy and Mitochondrial Function in Muscle and Liver Samples - Inoue, Kenji; Kato, Takeo; Terasaki, Eisuke; Ishihara, Mariko; Fujii, Tatsuya; Aida, Yuko; Murayama, Kei (Neuropediatrics, 2024)
X-linked myotubular myopathy (XLMTM) is a rare congenital myopathy that commonly manifests with liver involvement. In most XLMTM cases, disease-causing variants have been identified in the myotubularin gene (MTM1) on chromosome Xq28, which encodes myotubularin protein (MTM1). The impairment of mitochondrial respiratory chain (MRC) enzyme activity in muscle has been observed in the XLMTM mouse model. Though several reports mentioned possible mechanisms of liver involvement in XLMTM patients and animal models, the precise underlying mechanisms remain unknown, and there is no report focused on mitochondrial functions in hepatocytes in XLMTM. We encountered two patients with XLMTM who had liver involvement. We measured MRC enzyme activities in two muscle biopsy specimens, and one liver specimen from our patients to investigate whether MTM1 variants cause MRC dysfunction and whether mitochondrial disturbance is associated with organ dysfunction. MRC enzyme activities decreased in skeletal muscles but were normal in the liver. In our patients, the impaired MRC enzyme activity found in muscle is consistent with previously reported mechanisms that the loss of MTM1-desmin intermediate filament and MTM1-IMMT (a mitochondrial membrane protein) interaction led to the mitochondrial dysfunction. However, our study showed that liver involvement in XLMTM may not be associated with mitochondrial dysfunction.
Keywords: X-linked myotubular myopathy; myotubularin protein; liver involvement; mitochondrial respiratory chain enzyme activity; mitochondrial dysfunction